Analysis of nostalgia sport tourism in football fans of Persian Gulf Pro League - Zare, S.; Zarei, A.; Tejari, F. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
The purpose of this study was to analyse nostalgia sport tourism in football fans of Persian Gulf Pro League. The sample of the study consisted of 210 football fans of Persian Gulf Pro League. The participants were selected through stratified random sampling. The Nostalgia Scale for Sport Tourism by Cho (2014) was used to collect the data. Confirmatory factor analysis of structural equations was used to analyse the hypotheses of the study. It was found that nostalgia has an effect on the behavioural intentions and attitude of football fans and that attitude has not a mediating role in the relationship between nostalgia and behavioural intentions of football fans. The nostalgia of the spectators is related to several factors, such as the sport environment and the experiences that the fans live together when they go to sport events. In conclusion, those football fans of Persian Gulf Pro League who have a positive attitude toward the football games may have better behavioural tendencies and, in the future, this can create nostalgic emotions.